Malnutrition as a Modifiable Risk Factor of Lower Respiratory Tract Infections Among Under Five Children - Mishra, P.; Parajuli, J.; Acharya, N.; Gupta, V (Journal of Nepalgunj Medical College, 2016)
Background: Pneumonia is the single largest cause of death in children worldwide. Malnutrition increases the incidence and severity of ALRI and similarly it contributes to malnutrition. By identifying and treating the cases of malnutrition will decrease disease burden. Objective: To identify malnutrition as a risk factor of lower respiratory tract infection among children of under five years. Methods and Materials: A case control study was conducted at Nepalgunj Medical College, Kohalpur Teaching Hospital, Kohalpur, Nepal from June 2014 to November 2014. All diagnosed case of ALRI as per WHO were selected for case group. The controls were healthy children presented in OPD, pediatric ward and immunization clinic. The predesigned case performa with check list was the tool to identifying risk factor of ALRI. All data were entered in SPSS version 19. Descriptive and analytic statistics were used for analysis of data with level of significance at p value <0.05. Results: 107 cases and 107 controls were enrolled with age and sex matched. Male to female ratio was 1.6:1 vs 1.8:1 and the proportion of infants, 70.1% vs 68.3% in cases and controls respectively. Moderate wasting was present on 36.4% (39) of case group and 16.8% (18) of control group and It was significantly associated with ALRI (p=0.003). 10.3% (11) of case group children were moderately stunted while 6.5% (7) of control group. It was not statistical associated with ALRI (p=0.325). Conclusions: Wasted children were more prone to suffer from ALRI as compare to stunted children. As it is modifiable risk factor, we should focus on effective community education and public health measures to prevent malnutrition. JNGMC Vol. 12 No. 2 December 2014. Page : 2-5